Morphology and anisotropy of thin conductive inkjet printed lines of single-walled carbon nanotubes. (23rd March 2017) - Torres-Canas, Fernando; Blanc, Christophe; Mašlík, Jan; Tahir, Said; Izard, Nicolas; Karasahin, Senguel; Castellani, Mauro; Dammasch, Matthias; Zamora-Ledezma, Camilo; Anglaret, Eric
Abstract: We show that the properties of thin conductive inkjet printed lines of single-walled carbon nanotubes (SWCNT) can be greatly tuned, using only a few deposition parameters. The morphology, anisotropy and electrical resistivity of single-stroke printed lines are studied as a function of ink concentration and drop density. An original method based on coupled profilometry-Raman measurements is developed to determine the height, mass, orientational order and density profiles of SWCNT across the printed lines with a micrometric lateral resolution. Height profiles can be tuned from 'rail tracks' (twin parallel lines) to layers of homogeneous thickness by controlling nanotube concentration and drop density. In all samples, the nanotubes are strongly oriented parallel to the line axis at the edges of the lines, and the orientational order decreases continuously towards the center of the lines. The resistivity of 'rail tracks' is significantly larger than that of homogeneous deposits, likely because of large amounts of electrical dead-ends.